1988
DOI: 10.1002/1097-0142(19880715)62:2<309::aid-cncr2820620214>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Dna ploidy is closely linked to tumor invasion, lymph node metastasis, and prognosis in clinical gastric cancer

Abstract: DNA ploidy microspectrophotometrically determined in 254 patients with gastric carcinoma was investigated from the standpoint of tumor invasion, lymph node metastasis, and prognosis. DNA distribution patterns were grouped into low and high ploidies. The 24.0% frequency in the high ploidy group, at the mucosal stage, increased in proportion to invasion into the deeper layers. There was a high incidence of lymph node metastasis in the high ploidy group, compared with the low ploidy group, in case of invasion bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 14 publications
3
29
0
1
Order By: Relevance
“…They were more advanced and had worse prognosis than diploid tumors and tumors with homogeneous ploidy [95,96,101].…”
Section: Molecular Alterations In Gastric Carcinomamentioning
confidence: 99%
“…They were more advanced and had worse prognosis than diploid tumors and tumors with homogeneous ploidy [95,96,101].…”
Section: Molecular Alterations In Gastric Carcinomamentioning
confidence: 99%
“…Furthermore, it has been reported that tumours with increased DNA content and a higher frequency of high-ploidy cells show higher mitotic rates. Such tumours are more likely to metastasise and invade surrounding tissues, and consequently their rate of resectability is low (Korenaga et al, 1988). Considering these findings, there seems to be a close relation between clinical and histological characteristics of HCC and nuclear DNA content.…”
Section: Discussionmentioning
confidence: 95%
“…The rate and capacity of proliferation of a cancer are considered to be predicting factors for biological malignant degree. Recently, immunostaining technique (Sasaki and Ogino, 1986;Danova, Mazzini et al, 1987;Hoshino, Prados et al, 1989;ROBBINS, Vega et al, 1987;Ploton, Menager et al, 1986;Crocker, 1990;Gerdes, Lemke et al, 1984;Lowe, Bodis et al, 1994;James, Richard et al, 1986;Korenaga, Okamura et al, 1988;Olga and Galina, 1998;Saito, Korenaga et al, 1991) that employs an antibody specific to an antigen (proliferating cell antigen), and is closely associated with the cell proliferation activity, have become available for predicting factors for proliferative capacity of a tumor. These markers includes BrdU (bromodeoxyuridine) (Hoshino, Prados et al, 1989), PCNA (proliferating cell nuclear antigen) (Robbins, Vega et al, 1987), AgNORs (Ploton, Menager et al, 1986;Crocker, 1990), Ki67 (Gerdes, Lemke et al, 1984), DNA histograms produced by flow cytometry (Sasaki and Ogino, 1986;Danova, Mazzini et al, 1987) or oncogenes, such as p53 (Lowe, Bodis et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the degree of malignancy of gastric cancer using a DNA histogram obtained by flow cytometry has shown that an aneuploidy DNA pattern is common in tumors that show a high level of cell proliferative activity, frequent lymph node metastasis and an especially marked tendency for deep-site infiltration (James, Richard et al, 1986;Korenaga, Okamura et al, 1988;Olga and Galina, 1998). In aspect of the tissue type of gastric cancers, it has been shown that there is a tendency that undifferentiated types have a rather higher level of susceptibility to anti-cancer agents than differentiated types (Saito, Korenaga et al, 1991).…”
Section: Annals Of Cancer Research and Therapymentioning
confidence: 99%